Finance students' experiences of lecture-based active learning tasks. Issue 1 (2nd January 2018) - McCullough, Kerry; Munro, Nicholas
Abstract: Consistent with current higher education concerns with student engagement and the student experience, this study explored third-year undergraduate Finance students' experiences of lecture-based active learning tasks. Finance students from the 2012 and 2014 cohorts from a South African university were invited to complete an anonymous questionnaire and participate in a focus group discussion. Most students affirmed the use of lecture-based active learning tasks, and highlighted how the related peer interactions and immediate application of Finance concepts were beneficial for their motivation and interest. In contrast, some students were disparaging of the lecture-based active learning tasks. Their dissenting views are incorporated as points of tension in the higher education teaching and learning process. The study also highlights the critical role that a passionate and student-centred teacher has on how active learning tasks are received by students during lectures, and generally on student engagement, student learning and the student experience.